Comparative Analysis Of Systems For Assessing Regional Impacts Of Innovations Applied To Coffee Production - Flavia Bliska; Celso Vegro; Thomaz Fronzaglia; Jamilsen Santos (European Regional Science Association (ERSA), 2012)
The importance of education, research and extension institutions, can be evaluated from the socio-economic impacts of their investments, capacity building and training of human resources, services rendered to the community and innovations resulting from their research. The knowledge and technologies generated in these institutions need to be transferred to the respective supply chains and increasingly used, to contribute in its development and environmental preservation. The dimensions of the regional impacts of these technologies is relevant to the strengthening of research institutions and to evaluate and update the guidelines of their programs. There are few studies in this area and most of them are linked to the analysis of the role of universities in the growth of the regions where they are located by calculating multipliers for employment, output and income. The evaluation of the environmental, social and economic impacts is even less significant, and emerged from the concept of sustainable development. In Brazil, progress in this area are derived primarily from studies of the Brazilian Agricultural Research Corporation (Embrapa) and from the State University of Campinas (Unicamp), who developed the systems known respectively Ambitec and ESAC, which in this study on coffee production in Brazil, held by the Agronomic Institute (IAC), are compared mainly from their scope, complexity and cost of implementation. Both consist of the ex-post analysis of the impacts of a particular technology and are built based on criteria and indicators. The application of those two systems indicated that the ESAC system involves a more complex software, and quantitative aspects more sophisticated than the Ambitec, and its use requires more intensive training of staff than Ambitec. A major difficulty of the analysis of impact assessments is to isolate the individual effects of technologies, effects resulting from their interactions with technologies developed by other R & D institutions, or even imported. The ability of the researcher to apply the questionnaires may reduce this problem. But the system ESAC presents an important advantage over the Ambitec because it considers two very important aspects for the analysis of impacts: the impacts resulting from the interactions between different technologies and the time elapsed between the development of technology and its adoption by the productive sector.
Keywords: 330; Impacts of technologies; Sustainable development; Regional development